Considering body mass differences, who are the world's strongest women? - Vanderburgh, P. M.; Dooman, C. (Medicine & Science in Sports & Exercise, 2000)
Purpose: Allometric modeling (AM) has been used to determine the world's strongest body mass-adjusted man. Recently, however, AM was shown to demonstrate body mass bias in elite Olympic weightlifting performance. A second order polynomial (2OP) provided a better fit than AM with no body mass bias for men and women. The purpose of this study was to apply both AM and 2OP models to women's world powerlifting records (more a function of pure strength and less power than Olympic lifts) to determine the optimal model approach as well as the strongest body mass-adjusted woman in each event. Methods: Subjects were the 36 (9 per event) current women world record holders (as of Nov., 1997) for bench press (BP), deadlift (DL), squat (SQ), and total (TOT) lift (BP + DL + SQ) according to the International Powerlifting Federation (IPF). Results: The 2OP model demonstrated the superior fit and no body mass bias as indicated by the coefficient of variation and residuals scatterplot inspection, respectively, for DL, SQ, and TOT. The AM for these three lifts, however, showed favorable bias toward the middle weight classes. The 2OP and AM yielded an essentially identical fit for BP. Conclusions: Although body mass-adjusted world records were dependent on the model used, Carrie Boudreau (U.S., 56-kg weight class), who received top scores in TOT and DL with both models, is arguably the world's strongest woman overall. Furthermore, although the 2OP model provides a better fit than AM for this elite population, a case can still be made for AM use, particularly in light of theoretical superiority.